STRATEGI PENGEMBANGAN BISNIS HALAL DI INDONESIA - Mundir, Abdillah; Mayang Sari Mufida; Noer Mochammad Fadli Robby (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The aim of writing this journal is to find out strategies for developing halal business in Indonesia. The writing method is descriptive based on previous research reports and several journals with the same theme, namely halal business development. The results of the review of several journals that have been listed can conclude that Indonesia has great potential to develop halal business globally. This is because the demand for halal products is increasing in every country. Not only that, but a halal business also requires several strategies to develop the business, namely by controlling product halalness, halal logistics, and halal verification.